The consequences of regular methamphetamine use in Tehran: qualitative content analysis - Javad Yoosefi Lebni; Arash Ziapour; Mostafa Qorbani; Fereshteh Baygi; Amin Mirzaei; Omid Safari; Babak Rastegarimehr; Bahar Khosravi; Morteza Mansourian (BMC, 2020)
Abstract Background In recent years, methamphetamine use has increased noticeably in Iran, and this can make harmful consequences for the health of individuals and society. Therefore, the study aimed to investigate the consequences of regular methamphetamine use in Tehran. Methods This study was conducted based on a conventional content analysis approach. Data were collected through observation and in-depth interviews with 20 regular adult users of methamphetamine in Tehran (including 15 males and 5 females). Participants were selected using snowball sampling and purposeful sampling, which continued until data saturation. Guba and Lincoln's criteria were used to assess the strength of the study. Results The extraction of the codes resulted in three main categories: (1)the short-term consequences, consisting of the sub-categories of individual and social consequences, (2) the long-term consequences, consisting of the sub-categories of psychological and physical consequences, high-risk behaviors, severely decayed memory and changes in the eating pattern, and (3) hallucinations and delusions including the sub-categories of visual and auditory hallucinations, persecutory delusions and delusion of having supernatural power. Conclusion Regular methamphetamine use may have serious adverse effects on the overall health of individuals. It is therefore highly recommended that educational programs must implement with the use of methamphetamine in the high- risk groups in order to raise awareness and change attitudes about the short and long term consequences. is highly recommended.